CITRA DALAM POLITIK KOTA: KAJIAN KOTA SURAKARTA 2005-2013 - Harsasto, Priyatno (JURNAL ILMU SOSIAL, 2015)
Local government leaders with good vision would have strong powers and new incentives for policyinnovation. In Surakarta local leaders have been playing crucial role in shaping new direction for urbandevelopment. In the name of political inclusion, they ask community groups as well business groups to involve inthe policy process. Based on a case study in Surakarta city, this report argues that the active role of localgovernment can be attributed as the broad explanation for the Surakarta cityâ€™s performance in urbandevelopment. This studyâ€™s findings suggest that government leadership is an important policy determinant that canshape the interests of the community and business. Vision â€œSolo Past is Solo Futureâ€ has been the rallying point ofthe local economic development. This vision has been able to be used to create cultural activities that has beendeterminant in bridging the interests of the society as a whole.